2017
DOI: 10.5937/industrija45-13548
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FDI on unemployment in transition countries: Panel cointegration approach

Abstract: This paper examines the relationship between FDI inflow per capita and unemployment rates in 17 transition countries over the period [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Usually, capital-intensive industries require primarily skilled workers and generate few jobs per dollar spent (Jenkins, 2006;Mahjabeen and Ataur, 2016). Our findings confirm Jude and Silaghi (2016)'s results on the negative impact of FDIs on employment in the short run, although marginal effects of the FDI alone on employment may not be a sufficient instrument to boost employment (Jude and Silaghi, 2016;Zdravkovic et al, 2017). Likewise, the results corroborate other empirical findings (Bayar, 2014(Bayar, , 2017 on positive impact of FDIs on the unemployment rate.…”
Section: Jedsupporting
confidence: 88%
See 3 more Smart Citations
“…Usually, capital-intensive industries require primarily skilled workers and generate few jobs per dollar spent (Jenkins, 2006;Mahjabeen and Ataur, 2016). Our findings confirm Jude and Silaghi (2016)'s results on the negative impact of FDIs on employment in the short run, although marginal effects of the FDI alone on employment may not be a sufficient instrument to boost employment (Jude and Silaghi, 2016;Zdravkovic et al, 2017). Likewise, the results corroborate other empirical findings (Bayar, 2014(Bayar, , 2017 on positive impact of FDIs on the unemployment rate.…”
Section: Jedsupporting
confidence: 88%
“…Similarly, in the context of 20 Caribbean countries, Craigwell's (2006) study found a positive impact of FDI inflow on the employment rate over the period 1990–2000 (Strat et al , 2015). Balcerzak and Zurek's (2011) study found a negative impact of FDI and unemployment over 1995–2009 (Zdravkovic et al , 2017). In the context of other countries, such as the USA (Ajaga and Nunnenkamp, 2008) and Fiji (Jayaraman and Singh, 2007), studies reported positive effects of inward FDIs on employment in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gligorić [11] points out that theoretical and empirical findings indicate the existence of a positive effect of FDI on economic growth, employment and exports. According to Zdravković et al [47], positive effects of FDI on macroeconomic indicators (GDP and employment) can be found in research papers published by Habib and Sarwar [15] for Pakistan, in the period from 1970 to 2011. Furthermore, Pindžo and Vjetrov [32] confirmed findings of Alfaro et al [1] whose research suggests that FDI played a fundamental role in contributing to economic growth (especially in terms of development of local financial markets).…”
Section: Literature Reviewmentioning
confidence: 99%